Level of contamination of environmental objects in rabbits farms by the propagal stages of Passalurus ambiguus - Khorolskyi, A.; Mushynskyi, A. (Scientific Progress & Innovations, 2022)
Contamination of environmental objects by propagative stages of development of pathogens of invasive diseases of animals and humans is one of the important factors of their transmission. Studies aimed at establishing the level and features of contamination of such objects as soil, litter, feed for farm animals, and scrapings from places of their keeping make it possible to timely, accurately, and effectively diagnose, predict and prevent outbreaks of parasitic diseases. The aim of the research was to establish the level of contamination of environmental objects in rabbit farms with exogenous sta ges of Passalurus ambiguus. The research was conducted in the conditions of individual farms of the Poltava region, unfavorable for rabbit pasallurosis, and on the basis of the laboratory of parasitology of Poltava State Agrarian University. The results of the soil tests show that the most contaminated soil was the litter soil taken from different layers in the area under the cages, where the average extensive contamination index was 52.22 %, and the intensive contamination index was 252.13 eggs/kg. With increasing distance from the cages where rabbits are kept, the level of soil contamination decreases to 23.33 % and 67.26 spec.eggs/kg – at a distance of 1 m, 14.44 % and 43.27 spec. eggs/kg – at a distance of 5 m. It was determined that with increasing depth of sampling, the rates of contamination with Passularis eggs decreased and amounted to: on the surface – 20.0–73.33% and 64.58–325.57 eggs/kg, at a depth of 5 cm – 13.33–56, 67% and 31.25–243.3 eggs/kg, at a depth of 10 cm – 10.0–26.67% and 16.67–68.75 eggs/kg. The level of contamination of scrapings from the cages where rabbits are kept was higher than the contamination of the soil. The average extensive contamination index was 81.67 %, and the intensive contamination index was 401.02 eggs/kg. Depending on the sampling sites, the the extensive contamination index ranged from 63.33 to 96.67 %, and the intensive contamination index ranged from 254.61 to 537.50 eggs/kg. The obtained results make it possible to effectively implement a set of measures to prevent environmental pollution by the propagative stages of Passalurus ambiguus.